КЕРУВАННЯ ДАНИМИ КОМЕРЦІЙНОГО ОБЛІКУ В УМОВАХ ЛІБЕРАЛІЗАЦІЇ РИНКУ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ УКРАЇНИ - Коцар, О.В.; Расько, Ю.О. (Інститут електродинаміки НАН України, Київ, 2019)
The liberalization of the electricity market aims, in particular, to stimulate market players towards energy-efficient behavior, mainly through widespread use of distributed generation based on alternative and renewable energy sources, efficient use of energy resources, and the real time matching of demand and proposals in the market. Finally this should help to reduce the use of fossil fuels and minimize the negative impact on the environment. The essential condition for effective use of market mechanisms for energy management is to ensure the accuracy, completeness, integrity, authenticity and relevance of metering data at the all points of commercial metering in the electricity market. Thearticle investigates the factors influencing the reliability of data metering at different stages of their formation in distributed smart systems for control, commercial metering and energy management, analyzes the experience of verification and validation the data of commercial metering in the wholesale and retail electricity markets of Ukraine, and are proposed the effective mechanisms for ensuring the reliability of commercial metering data in conditions of liberalization of the electricity market of Ukraine.References 10, tables 3, figures 6.